Cucurbit plant defenses against aboveground or belowground insect herbivores are distinct and shaped by eco-evolutionary factors - Morgan N. Thompson; Emily M. Russavage; Jeremy G. Garces; B. Jack Bradford; Danielle Merrell; Charles P.-C. Suh; Anjel M. Helms (Basic and Applied Ecology)
Plant defense strategies against insect herbivores are classified broadly as resistance or tolerance. Resistance deters insect growth or feeding, while tolerance mitigates negative effects of herbivory on plant fitness. Plant investment into resistance or tolerance strategies likely falls along a continuum that has been shaped by eco-evolutionary factors, such as plant domestication or coexistence histories with herbivores. Relatively little is known about how general defense strategies differ against aboveground foliar herbivores and belowground root herbivores. In the current study, we investigated defense strategies of plant species in the gourd family (Cucurbitaceae) against aboveground squash bug (Anasa tristis) or belowground striped cucumber beetle (Acalymma vittatum) herbivory. We selected six cucurbit plant species that differed in domestication status and coexistence history with herbivores: zucchini squash (Cucurbita pepo subsp. pepo); Texas gourd (Cucurbita pepo subsp. texana); pumpkin (Cucurbita maxima); buffalo gourd (Cucurbita foetidissima); cucumber (Cucumis sativus); and watermelon (Citrullus lanatus). For each plant species and herbivore combination, we conducted separate resistance and tolerance assays. We also carried out a field experiment to examine how longer-term herbivory influences plant reproductive and vegetative growth. We observed variation in resistance among cucurbit plant species against aboveground and belowground herbivory. Across species, plants were generally more tolerant of herbivory belowground than aboveground. We determined that wild plants were more resistant than domesticated counterparts to herbivory aboveground but not belowground. Further, plants with an herbivore coexistence history were less resistant to herbivory aboveground and belowground compared to those without. With longer-term herbivory in the field, zucchini plants were more tolerant of either aboveground or belowground herbivory than watermelon plants. Collectively, our findings highlight differences in plant defense against aboveground and belowground herbivores, advancing understanding of the eco-evolutionary factors shaping plant defense strategies and providing new insights for agricultural pest management in cucurbits.